Changes in specific microbial groups characterize the impact of land conversion to oil palm plantations on peat - Azizan, Siti Noor Fitriah; Murakami, Shuichiro; McTaggart, Iain; Yusof, Nurtasbiyah; Sha’arani, Shazwana; Hara, Hirofumi; Noborio, Kosuke (Frontiers in Forests and Global Change, 2024)
The conversion of tropical peat swamp forests to oil palm plantations has become a focal point in relation to global change. However, it is difficult to understand the ecological consequences of this conversion because little is known about how the microorganisms in these ecosystems respond to land-use conversion. Therefore, in this study, we assessed the microbial community structures of tropical peatland under two land uses, peat swamp forest and oil palm plantation (OP), to investigate how changes in local environmental conditions due to the conversion from forest to OP may have affected the microbial communities. For each land use, the microbial communities were assessed at three depths (0–5 cm, 20–25 cm, and 40–50 cm) using meta-16S amplicon analysis with Illumina Miseq. We found that the microbial communities under both land uses were dominated by anaerobes and fermenters, such as Acidobacteriota, Proteobacteria and Actinobacteria, which accounted for 80%–90% of the total abundance. There were strong similarities between the microbial communities in the 0–5 cm forest samples and the OP samples at all depths. However, the microbial communities in the 20–25 cm and 40–50 cm forest samples were different from the other samples. The differences in the deeper forest samples were likely related to water table and peat quality. CO2 fluxes from the forest were significantly higher than from OP, with mean fluxes of 190 ± 66.92 and 57.86 ± 33.66 mg m−2 h−1, respectively (p < 0.05). However, there were no differences in either CH4 or N2O fluxes between the forest and OP. We detected nine microbial taxa that characterized the differences in the microbial communities between the forest and OP (p > 0.05); Bathyarchaeia, Dadabacteriales, Syntrophobacter, and Subgroup_13 were significantly more abundant in the forest, especially in the deeper peat layers, whereas Acidobacter, Bryobacter, 11–24, Leptospirillum, and WPS-2 were significantly more abundant in the OP (p > 0.05). This study helps improve our understanding of the differences in microbial community structures between peat swamp forests and OP systems.